Safety of ACEI/ARB use in the early (<3 months) post kidney transplant period: a systematic review and meta-analysis - Fu, Dahai; Li, Jin; Zeng, Guanglan; Tang, Maozhi (Frontiers in Pharmacology, 2024)
Background: Data about the safety of ACEI/ARB use in early (<3 months) posttransplant period are restricted and remain controversial.Methods: This systematic review and meta-analysis included searches of PubMed, Embase and CENTRAL from inception to 31 Nov 2023, for studies to compare the safety (transplant outcomes and postoperative complications) of ACEI/ARB with non-ACEI/ARB (other antihypertensive medications) initiation in early post kidney transplant period.Results: Of 1247 citations identified, 13 eligible studies involving 1919 patients were enrolled for analyses. In short-or long-term observations, there were no differences on pooled serum creatinine between ACEI/ARB and non-ACEI/ARB groups whether initiated within 1 or 1-3 months posttransplant, however, initiation of ACEI/ARB within the first month posttransplant had an advantage effect on the mean creatinine clearance. Early initiation of ACEI/ARB posttransplant reduced the risks of patient death (RR 0.60, p=0.009) and graft loss (RR 0.54, p=0.0002). For postoperative complications, there were no significant differences in acute rejection risk (RR 0.87, p=0.58), delayed graft function risk (RR 1.00, p=0.93), hemoglobin level (MD -0.32 mg/Dl, p=0.46) or urinary protein excretion (MD -0.10 g/24h，p=0.16) between two groups. However, the ACEI/ARB group had higher incidence of hyperkalemia (RR 2.43, p=0.02).Early initiation of ACEI/ARB within 3 months posttransplant proved to be basically safe and has renal function recovery benefits, however, hyperkalemia needs to be noted.